2016
DOI: 10.1007/s00705-016-2785-z
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyl transferase 2 polymorphism may be associated with enterovirus 71 severe infection in a Chinese population

Abstract: Genetic polymorphism in the carnitine palmitoyl transferase 2 (CPT2) gene has been reported to be a susceptibility factor in a number of syndromes of acute encephalopathy with various infectious diseases, but evidence of its effect on enterovirus 71 (EV71) infection is lacking. The goal of this study was to examine the relationship between genetic polymorphism of CPT2 and severity of EV71 infection in a Chinese population. PCR of five exons of the CPT2 gene was carried out to identify single-nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Some polymorphisms of EV71 receptors (such as TLR3 and TLR4) have been shown to be involved in the inflammatory pathogenesis of EV71 infection 6,17 . Genetic polymorphisms of some inflammatory mediators (such as OAS3, IL‐4 , and CPT2 ) have also been shown to be associated with susceptibility to EV71 infection 5,18–21 . Evidence that host genetic polymorphisms affect the susceptibility and severity of EV71 infection is increasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some polymorphisms of EV71 receptors (such as TLR3 and TLR4) have been shown to be involved in the inflammatory pathogenesis of EV71 infection 6,17 . Genetic polymorphisms of some inflammatory mediators (such as OAS3, IL‐4 , and CPT2 ) have also been shown to be associated with susceptibility to EV71 infection 5,18–21 . Evidence that host genetic polymorphisms affect the susceptibility and severity of EV71 infection is increasing.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 17 Genetic polymorphisms of some inflammatory mediators (such as OAS3, IL‐4 , and CPT2 ) have also been shown to be associated with susceptibility to EV71 infection. 5 , 18 , 19 , 20 , 21 Evidence that host genetic polymorphisms affect the susceptibility and severity of EV71 infection is increasing. IRAK4 is indispensable for responses to IL‐1 and ligands that stimulate various TLRs; therefore, it plays a significant role in mediating the innate immune response induced by EV71.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many association studies between host genetic factors and EV71 infection have been performed. Our lab has previously demonstrated that polymorphisms in genes of IL-8, IL-10, IFN-γ, IL-6, IL-4, CXCL-10, CCL-2, TLR3, OAS3 and CPTII were associated with the susceptibility and/ or the severity of EV71 infection [24][25][26][27][28][29][30][31][32]. These cytokines/ chemokines and receptors are all necessary for an efficient inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have mainly focused on exploring the relationship between EV71 infection and host immunity at the molecular level, and it has been found that human gene polymorphisms, such as those of CPT2, OAS2, and IL-17F, are related to infection susceptibility and severity. [5][6][7][8][9] The transmembrane protein 173 (TMEM173), also known as MPYS, mediates the interferon regulatory factor 3 (IRF3) activation (MITA), endoplasmic reticulum interferon stimulator (ERIS), stimulator of interferon genes (STING), and stimulator of interferon response cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) interactor 1 (STING1). Human TMEM173 is located on chromosome 5q31.2, contains eight exons, and encodes a transmembrane protein between the endoplasmic reticulum and Golgi in response to the presence of cytosolic dsDNA as well as an adaptor protein that mediates the production of type I interferon.…”
Section: Introductionmentioning
confidence: 99%